Assessment of knowledge, attitude, and practice of antibiotics prescription among healthcare residents at King Abdulaziz medical City, Jeddah, Saudi Arabia - Areej Alowfi; Rana Alghamdi; Dhai Albogami; Laila Bukhari; Muhammad Anwar Khan; Lujain Almarhoumi (Elsevier, 2023)
Introduction: Antibiotic resistance (ABR) is defined as bacteria's resistance to therapy despite therapeutic levels of antibiotics. It is a global health concern. Data on the antibiotic prescription practice of physicians, in general, are limited in Saudi Arabia. Therefore, we aim to assess the knowledge, attitude, and practice of antibiotic prescription between surgical and non-surgical residents at King Abdulaziz Medical City (KAMC). Methods: A cross-sectional study was conducted at KAMC in Jeddah, Saudi Arabia, from September 2019, until March 2020. The questionnaire contained demographic information and 31 questions based on the studied variables: knowledge (17), attitude (4), and practice (10). Results: The response rate was 83 %. Male to female response rates were 54 % and 46 %, respectively. The majority of respondents (72 %) were non-surgical residents. Positive practice skills showed that 55 % of all healthcare residents always used practice guidelines for antibiotic prescription in their daily work (P-value < 0.001). Most residents (50 %) sometimes used delayed prescriptions. Non-surgical residents discussed ABR with patients more than surgical residents (P-value = 0.028). Lack of patient interest was the common cause for not discussing ABR with patients (42 %). Non-surgical residents had significantly more training on antibiotic prescription (p-value = 0.001). The fear of infection spread due to not prescribing an antibiotic was significantly higher in non-surgical residents (P-value < 0.001). Non-surgical residents (76 %) took a past medical history of antibiotic consumption more than surgical residents (24 %) (P-value = 0.003). Antibiotic prescription for residents was not influenced by advertisements (91 %). The most common resistant organisms reported by residents were insignificant between the two groups. The results also showed that the residents' common choice of antibiotics was not statistically different between surgical and non-surgical residents in most antibiotic classes. Conclusions: We found that practice guidelines, formal training, and taking patients' past medical histories were significantly higher among non-surgical residents. In contrast, surgical residents were prescribing more antibiotics due to the fear of the spread of the infection. Proper training is essential for all healthcare residents to overcome differences among different specialties.